2023
DOI: 10.2460/javma.22.12.0596
|View full text |Cite
|
Sign up to set email alerts
|

Age at gonadectomy, sex, and breed size affect risk of canine overweight and obese outcomes: a retrospective cohort study using data from United States primary care veterinary clinics

Abstract: OBJECTIVE To examine the risk of developing an overweight or obese (O/O) body condition score (BCS) in gonadectomized versus intact dogs and, separately, the impact of age at gonadectomy on O/O outcomes among sterilized dogs. ANIMALS Dogs were patients of Banfield Pet Hospital in the US from 2013 to 2019. After exclusion criteria were applied, the final sample consisted of 155,199 dogs. PROCEDURES In this retrospective cohort study, Cox proportional hazards models evaluated associations between O/O and gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Owners of dogs in this population were offered various wellness plans, which consist of prepaid packages of services that can reduce the cost of clinic visits and some diagnostic tests, including radiographs. Enrollment in such a wellness plan has previously been suggested to be a risk factor for detection bias ( 38 ), and in this study, it was strongly associated with OA diagnosis. Dogs with a wellness plan had far more clinic visits and were more likely to have radiographs than dogs not enrolled in such a plan (data not shown), likely leading to a higher rate of detection of OA.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Owners of dogs in this population were offered various wellness plans, which consist of prepaid packages of services that can reduce the cost of clinic visits and some diagnostic tests, including radiographs. Enrollment in such a wellness plan has previously been suggested to be a risk factor for detection bias ( 38 ), and in this study, it was strongly associated with OA diagnosis. Dogs with a wellness plan had far more clinic visits and were more likely to have radiographs than dogs not enrolled in such a plan (data not shown), likely leading to a higher rate of detection of OA.…”
Section: Discussionsupporting
confidence: 54%
“…Both weight and desexing are independent risk factors of OA. However, it has been reported that dogs that are desexed may be more likely to develop obesity ( 22 , 38 ), which may increase the risk of OA. To test if the influence of higher body weight on OA-free survival differed by desexing status, the interaction between adult weight and desexing status was tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation